The Role of Parents in Stimulating Early Children's Language Development Through Smartphone Use - Nasratun Najiha; Ilma Zulfina; Fifi Elvia; Muarofakh; Ahmadi Cahyadi (JOYCED: Journal of Early Childhood Education, 2023)
Language is a relatively essential means of communication to pay attention to and develop in early childhood, starting from children who have not yet learned the sounds of language, the vocabulary of letters and phrases, to assembling simple sentences. In this case, parents, teachers, and the surrounding community are responsible for children's language development through digital media, one of which is media use. This study aims to describe the role of caregivers in stimulating children's language development through smartphone media. The type of research used is descriptive qualitative, through primary data as a source of research data originating from related parties obtained from respondents; this study uses a questionnaire data collection technique with two closed answers (yes/no) and is equipped with open questions obtained online through the Google forms platform. The data analysis technique is an interactive model carried out through three stages: data reduction, presentation, and verification. The results of this study explain that the use of wise parental supervision will be more effective and effective in increasing the stimulation of children's language development because parents control every child's activity at home. It can be seen from the duration of use. In early childhood, it reaches 47% in the range of 2-3 hours per day, and the application often used by children is YouTube as a way for children to gain mastery of language both orally and in writing. The study results show that caregivers' role in stimulating children's language development is crucial; this can be proven by children who think broadly and are skilled at communicating.